2019
DOI: 10.1002/jrsm.1353
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparison of univariate and multivariate meta‐analyses in Cochrane Pregnancy and Childbirth reviews with multiple binary outcomes

Abstract: Background Multivariate meta‐analysis (MVMA) jointly synthesizes effects for multiple correlated outcomes. The MVMA model is potentially more difficult and time‐consuming to apply than univariate models, so if its use makes little difference to parameter estimates, it could be argued that it is redundant. Methods We assessed the applicability and impact of MVMA in Cochrane Pregnancy and Childbirth (CPCB) systematic reviews. We applied MVMA to CPCB reviews published between 2011 and 2013 with two or more binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Multivariate meta–analyses for secondary outcome domains also included all available time point ranges, but data from our IPD were less suitable to estimate between–outcome within–study correlations and no IPD were available, so meta–analyses were outcome–specific. Within–study correlations were bypassed using Riley’s method as our IPD were unsuitable [ 66 ]; for cognitive functioning, this method had to be rejected due to extreme correlations, so a within–study correlation of 0.75 was imputed (high given the outcome–specific analysis) with a sensitivity analysis testing 0.5 [ 67 ]. Results of meta–analyses containing few studies were interpreted cautiously, including multivariate meta–analyses with outcomes derived from a single trial.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate meta–analyses for secondary outcome domains also included all available time point ranges, but data from our IPD were less suitable to estimate between–outcome within–study correlations and no IPD were available, so meta–analyses were outcome–specific. Within–study correlations were bypassed using Riley’s method as our IPD were unsuitable [ 66 ]; for cognitive functioning, this method had to be rejected due to extreme correlations, so a within–study correlation of 0.75 was imputed (high given the outcome–specific analysis) with a sensitivity analysis testing 0.5 [ 67 ]. Results of meta–analyses containing few studies were interpreted cautiously, including multivariate meta–analyses with outcomes derived from a single trial.…”
Section: Methodsmentioning
confidence: 99%
“…The differences between the results of the current study and those referenced above [8,14,[89][90][91][92][93] needs some further explication with regard to data structure. The bi-and tri-variate meta-analyses under consideration were relatively conventional; a primary mortality outcome and second and third recorded outcomes which were not direct extensions of the primary outcome.…”
Section: Discussionmentioning
confidence: 67%
“…Frequentist and Bayesian empirical comparisons between univariate meta-analyses and MVMA have appeared in the literature [8,14,[89][90][91][92][93] with results demonstrating similar (pooled) parameter estimates between the two analytic forms. However, papers by Riley and co-workers [1,15,24,94], which included formal simulation studies, found advantage; a smaller standard error and mean-square error of pooled estimates, predicated upon the presence of missing data; again, assuming missing at random.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations